Teaching leadership with popular culture: Practical lessons from Harry Potter. (3rd April 2022) - Yu, Helen H.; Lorenzo-Elarco, Kenika M.; Murro, Mary J.; McAnany, Elisabeth L.; Anderson, Hana R.
ABSTRACT: The scholarship on using popular culture – specifically from films – as an effective educational tool to enhance teaching opportunities that link leadership theory to practice has gained traction in the past decade. This article extends the discourse and uses Harry Potter, the cultural phenomenon fantasy film series, as a source of teaching material apt with practical lessons in leadership. A content analysis of the 8-film series found 151 leadership scenarios that can be used as models in which leadership theories and approaches can be recognized, applied, and promote classroom discussion. However, seven specific clips are showcased to recognize a limited number of leadership theories and approaches frequently taught in a public affairs leadership classroom. They include the situational and behavioral approaches to leadership, leader-member-exchange theory, authentic leadership, team leadership, transformational leadership, and race/culture in leadership.